Developing Creative Teaching Skills in Pre-Service Teachers - Simpson, Rachel; Newton, Douglas P.; Newton, Lynn (International Journal for Talent Development and Creativity, 2022)
Teaching is an interactive process as teachers respond to diverse interests and needs of learners, alongside the changing demands of education systems. Giving teachers the opportunity to develop competence in creative teaching may enable them to prepare and improvise teaching to maximise learning. A package to foster creative teaching through various learning experiences was constructed and tested on pre-service teachers. The effect of the package on seventy-two pre-service teachers was assessed, largely by quantitative pre and post-tests and qualitative responses. This was supplemented by data from similar teachers who did not have this opportunity. There was strong evidence of worthwhile increases in the pre-service teachers’ understandings and use of creative teaching approaches following their completion of the development package. Interview data suggested that a beneficial impact extended into the teachers’ first year of teaching, and that creative teaching can become a part of teacher identity. The article describes evidence that creative teaching can be fostered and it concludes with a recommendation that teacher training and development should give it explicit attention. Some challenges and potential solutions are described.